Exploring the Barriers of Home Care Services in Iran: A Qualitative Study - Heshmatolah Heydari; Hooman Shahsavari; Abdolrahim Hazini; Alireza Nikbakht Nasrabadi (Scientifica)
With increasing chronic diseases, the use of home care is rising in the world. Home care in Iran has many challenges and to improve that, we should identify the challenges and barriers of home care. The aim of this study was to identify and explore the barriers of home care in Iran. This is a qualitative study with content analysis approach that was conducted in Iran in 2015. Fourteen key informants comprising health policymakers, faculty members, nurses, and physicians as well as patients and families engaged in home care purposefully participated in this study. Data was obtained using face-to-face semistructured interviews. A focus group discussion was also used to complete the findings. Graneheim and Lundman’s approach was used for analysis of data and Lincoln and Guba’s criteria were used to confirm the trustworthiness of study’s findings. The data were divided into three main categories and eight subcategories. Main categories included treatment-based approach in the healthcare system, cultural dimensions, and the lack of adequate infrastructure. A position for home care in the healthcare system, considering cultural dimensions in Iranian society and providing an appropriate infrastructure, can be beneficial to improve the situation of home care services in Iran.